ANALISIS TINGKAT STRES KERJA SERTA COPING STRES PADA PEGAWAI REKAM MEDIS DI RSUD K.R.M.T. WONGSONEGORO KOTA SEMARANG - Rizqika Aza P.P; Ida Wahyuni; Ekawati Ekawati (Jurnal Kesehatan Masyarakat (Undip), 2017)
The hospital is a health services that is absolutely required by all levels of society in an effort to improve the health status of both individuals and society as a whole. To fulfill these needs, the hospital is required to provide adequate and satisfactory service.Therefore, the hospital must be able to improve the quality of its services, including improving the quality of documenting medical records. The purpose of this study was to analyze the level of work stress and coping stress used by medical record employment section coding. In addition, this study was to determine of physical and mental workload and fatigue of employees of coding. The type of this research was qualitative descriptive research. The population of this study was the employee medical record of the coding section amounted to 11 people with total sampling method. The data were collected using an in-depth interview questionnaire about stress coping and measurement of physical, mental, fatigue, and work stresswith Pulsemeter, NASA-TLXquestionnaire, Deary-Liewald Reaction Time Task Application, and HARS questionnaire. Data analysis had done descriptively to understand the phenomenon about what is experienced by research subject. The conclusion of this research is employees who have moderate work stress level using problem-focused coping strategy whereas employees with high work stress level use emotional-focused coping strategy to deal with stressors.